Neonatal hypoglycaemia: learning from claims. Issue 2 (23rd August 2016) - Hawdon, Jane M; Beer, Jeanette; Sharp, Deborah; Upton, Michele
Abstract : Objectives: Neonatal hypoglycaemia is a potential cause of neonatal morbidity, and on rare but tragic occasions causes long-term neurodevelopmental harm with consequent emotional and practical costs for the family. The organisational cost to the NHS includes the cost of successful litigation claims. The purpose of the review was to identify themes that could alert clinicians to common pitfalls and thus improve patient safety. Design: The NHS Litigation Authority (NHS LA) Claims Management System was reviewed to identify and review 30 claims for injury secondary to neonatal hypoglycaemia, which were notified to the NHS LA between 2002 and 2011. Setting: NHS LA. Patients: Anonymised documentation relating to 30 neonates for whom claims were made relating to neonatal hypoglycaemia. Dates of birth were between 1995 and 2010. Interventions: Review of documentation held on the NHS LA database. Main outcome measures: Identifiable risk factors for hypoglycaemia, presenting clinical signs, possible deficits in care, financial costs of litigation. Results: All claims related to babies of at least 36 weeks' gestation. The most common risk factor for hypoglycaemia was low birth weight or borderline low birth weight, and the most common reported presenting sign was abnormal feeding behaviour. A number of likely deficits in care were reported, all of which were avoidable. In this 10-year reporting period, there were 25 claims for which damages were paid, with a total financial cost of claims to the NHS of £162 166 677. Conclusions: Acknowledging that these are likely to be the most rare but most seriously affected cases, the clinical themes arising from these cases should be used for further development of training and guidance to reduce harm and redivert NHS funds from litigation to direct care.